Notes on the Origin of Jorge Luis Borges’ Bartolomé de Las Casas - Ricardo Monsalve (Литература двух Америк)
The 1935 short story collection A Universal History of Iniquity is a foundational stone in Jorge Luis Borges’ (1899–1986) remarkable narrative career. Its first tale, “The Cruel Redeemer Lazarus Morell,” prefigures some of the Argentine’s stylistic peculiarities and lifelong thematic inclinations, which continue to spur specialized scholarship today. Cultural and literary critics alike have studied the story’s opening allusion to the Dominican friar Bartolomé de Las Casas (1484–1566) to claim that the Spanish priest mirrors the murderous life of Lazarus Morell (Lawrence; Warnes), thus showing the often-problematic connections between North and South American history (Waisman; Green). Such scholarship, however, has uncritically accepted Borges’ traditional view of Las Casas as the original instigator of African slavery in the New World. Similarly, the source of this customary view has yet to be addressed in depth. This brief article postulates a clear source for Borges’ literary portrait of Las Casas by tracing and contrasting some of the author’s well-known personal readings. It ultimately suggests that Borges derives his character both from the entries concerning slavery in the prestigious Encyclopædia Britannica (1911), as well as from William Robertson’s (1721–1793) historiographical work on the Americas. The conclusion likewise shows that Borges consciously distorted Las Casas’ historical record in order to fit the Universal History’s aesthetic project.